Social Relation Cognitive Model on Virtual Prototyping Technology in Construction Project - Zhang, Lei; Liu, Honglei; Wang, Guangbin (International Journal of Online and Biomedical Engineering (iJOE), 2013)
It is valuable to study social relation cognition of participants about virtual prototyping technology in construction projects to promote its acceptance and application. Building information modeling (BIM) is a transformative virtual prototyping technology for construction industry. The analysis of social relation is closely related to BIM application to stakeholders, which involves many cognitive indicators, i.e. organizations, spaces and behaviors. Based on social network analysis, a cognitive model for actorsâ?? social relation to BIM knowledge is proposed?Using survey data, this paper explores the cognitive ability between participants. Through statistical analysis of indictors in the model, it is found that significant difference of virtual prototyping technology in social relation cognition exists.